Continuum of Care for Inmates Taking Psychiatric Medications While Incarcerated in Minnesota County Jails. (October 2017) - Rohrer, Brittney; Stratton, Timothy P.
Mental illness is more prevalent among adult inmates in Minnesota county jails than nationally. All 78 Minnesota county jails were surveyed about their continuum-of-care procedures to help ensure that inmates who have mental illness continue to receive psychiatric medications after release. Of the 28 county jails responding to the survey (36%), most estimated that greater than 40% of their inmates receive medication for mental illness during incarceration. But while 89% of respondents reported that inmates are frequently taking medication(s) to treat mental illness at release, prerelease planning for these inmates was rarely undertaken. Few Minnesota jails reported having continuum-of-care procedures in place for inmates who have mental illness when these inmates are released back into the community. Jail staff desire greater collaboration between jails, human services agencies, and community mental health providers to help support discharge planning and enhance the continuum of care for inmates who have mental illness.